2021
DOI: 10.1007/s00122-021-03844-9
|View full text |Cite
|
Sign up to set email alerts
|

OsCOP1 regulates embryo development and flavonoid biosynthesis in rice (Oryza sativa L.)

Abstract: Key message Novel mutations of OsCOP1 were identified to be responsible for yellowish pericarp and embryo lethal phenotype, which revealed that OsCOP1 plays a crucial role in flavonoid biosynthesis and embryogenesis in rice seed. Abstract Successful production of viable seeds is a major component of plant life cycles, and seed development is a complex, highly regulated process that affects characteristics such as seed viability and color. In this study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 92 publications
(139 reference statements)
0
11
0
Order By: Relevance
“…6 F; Additional file 1 : Fig. S6A), and their family members have been reported to regulate organ development [ 45 47 ]. No che-RNA-associated motif was detected in che-lncNAT OsCHENAT1709 .…”
Section: Resultsmentioning
confidence: 99%
“…6 F; Additional file 1 : Fig. S6A), and their family members have been reported to regulate organ development [ 45 47 ]. No che-RNA-associated motif was detected in che-lncNAT OsCHENAT1709 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we previously identified three Arabidopsis “ fusca ”-like cop1 null mutants ( yel - hc , yel - sk , and yel - cc ) in rice. These mutants carry loss-of-function alleles of OsCOP1 and share several phenotypic characteristics with the yel - sdj mutant, including embryonic lethality and high-level flavonoid accumulation in the pericarp and embryo ( Kim et al, 2021 ). Similarly, the Arabidopsis det1 null mutant displays the phenotypic characteristics of strong cop1 mutant alleles, such as short hypocotyls, opened cotyledons, and anthocyanin accumulation ( McNellis et al, 1994 ; Misera et al, 1994 ; Pepper et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported the "fusca"-like cop1 null mutants in rice, which we named as yellowish-pericarp embryo lethal (yel), and showed that the corresponding gene, OsCOP1, regulates flavonoid biosynthesis and embryo development. However, the effect of COP1 mutation on embryo development and pigmentation in rice was different from that in Arabidopsis; unlike the Arabidopsis fus mutants, which exhibited seedling lethality and anthocyanin accumulation in the cotyledons, the rice yel mutants showed embryonic lethality and flavonoid accumulation in the embryo and pericarp (Kim et al, 2018(Kim et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…This not only turned the pericarp of the rice variety yellowish but also caused embryonic death. Moreover, this also reduced the size of the transgenic seeds [98]. According to a study, a total of 82 flavonoids have been chemically identified in transgenic rice seeds.…”
Section: Flavonoids In Rice Breedingmentioning
confidence: 99%